User Tools

Site Tools


var_x_y

우선 variance는 아래와 같이 계산될 수 있다.
\begin{eqnarray*} Var[X] & = & {E{(X-\mu)^2}} \\ & = & E[(X^2 - 2 X \mu + \mu^2)] \\ & = & E[X^2] - 2 \mu E[X] + E[\mu^2] \\ & = & E[X^2] - 2 \mu E[X] + E[\mu^2], \;\; \text{because E[X]=} \mu \text{, \; E[} \mu^2 \text{] = } \mu^2, \\ & = & E[X^2] - 2 \mu^2 + \mu^2 \\ & = & E[X^2] - \mu^2 \;\;\; \dots\dots\dots\dots\dots\dots\dots\dots [1] \end{eqnarray*}

그리고
Event X와 Y가 독립적(independent) 이라고 하고
\begin{eqnarray*} E[X] & = & \mu_{X} = a \\ E[Y] & = & \mu_{Y} = b \end{eqnarray*} 이라고 하면

\begin{eqnarray*} Var [X + Y] & = & E[(X+Y)^2] - (a+b)^2 \\ & = & E[(X^2 + 2XY + Y^2)] - (a^2 + 2ab + b^2) \\ & = & E[X^2] + E[2XY] + E[Y^2] - (a^2 + 2ab + b^2) \\ & = & E[X^2] + 2E[XY] + E[Y^2] - (a^2 + 2ab + b^2) \;\;\text{because}\;\; E[XY] = E[X]E[Y] \\ & = & E[X^2] + 2ab + E[Y^2] - (a^2 + 2ab + b^2) \\ & = & E[X^2] + 2ab + E[Y^2] - a^2 - 2ab - b^2 \\ & = & E[X^2] + E[Y^2] - a^2 - b^2 \\ & = & E[X^2] - a^2 + E[Y^2] - b^2 \\ & = & Var[X] + Var[Y] \\ \end{eqnarray*}

var_x_y.txt · Last modified: 2019/10/20 01:10 by hkimscil